Pengaruh Beban Pajak, Likuiditas, Ukuran Perusahaan Terhadap Profitabilitas (Studi pada Perusahaan Otomotif yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2020) - Anggi Pratiwi Sitorus; Rolita Christina Purba; Budianto (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The purpose of this study was to examine the effects of tax burden, liquidity, and firm size on profitability. The population of this study is automotive companies listed on the Indonesian Stock Exchange for the period 2017-2020. The number of samples used is 48 companies by the saturated extraction method. The data processing program uses SPSS (Static product and service solution) version 25. The analytical methods used in this study are descriptive statistical tests, classical assumption tests, multiple linear regression, t-statistic tests, and F-statistics. test, certainty test (R2) and correlation test (r). Results showed that the tax burden variable had a negative impact on profitability. Liquidity has a clear positive effect on profitability. The firm size variable has a negative impact on profitability. Based on the simultaneous test (F-test), the profitability of automobile companies listed on the Indonesia Stock Exchange will be affected along with tax burden, liquidity and company size variables from 2017 to 2020.